Germany's dual constitution : parliamentary democracy in the Federal Republic - Meinel, Florian (London [England] : Hart Publishing, 2021)
"This book offers a compelling and persuasive framework for understanding the German constitutional system. It argues that it can only be fully understood as a dual structure combining two layers with little in common. The first layer is the basic administrative institutional structure, comprised of federal institutions. The second layer is that of parliamentary democracy. It is the interplay between the two, as mediated by the chancellery, the major political parties and the Federal Constitutional Court, which lies at the heart of the German constitutional arrangement. This innovative hybrid perspective allows for a better understanding of the current challenges of parliamentary government and its potential long-term development. An updated translation of its impactful German edition, this provides one of the most brilliant introductions to governmental systems of one of the world's most influential states."--
Includes bibliographical references.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Constitutional law -- Germany; Democracy -- Germany; Comparative law; Germany -- Constitutional law; Electronic books